Paraty the estrada real: the chemistry of cachaça aging - de Souza Monteriro Filho, Elias; Ramos da Luz, Angelica; Natale Junior, Raul; Ruiz, Miguel; Bosco Faria, João; Munich, Sinara; B. Adaime, Martha; Antonio Perazolli, Leinig (Seven Editora, 2023)
Since the development of the Gold Cycle, Paraty has shown prominence in the production of cachaça, which was consumed both by the national market and by slaves in Africa and by gold in the mines, being transported by the Estrada Real. The transport was carried out in oak barrels outside the country and in national wood barrels for the local market. Over time it was observed that each type of wood incorporated different odors and flavors to the cachaça. Considering that the cachaça is produced from the fermentation of the juice, different from the Rum, which is produced from the fermentation of molasses, and that the aging in different types of wood added specific sensory and chemical characteristics, allowed to establish the Cachaça as a genuinely Brazilian product. DOI: 10.56238/pacfdnsv1-047